PELATIHAN PEMBUATAN SABUN CUCI PIRING SEBAGAI UPAYA PENINGKATAN KETERAMPILAN MASYARAKAT DI KELURAHAN SITINJAK - Nasution, Nurul Hidayah; Harahap, Olivia Feby Mon; Harahap, Raja MP; Parlindungan, Muhammad Thohir; Nur, Muhammad; nisyah, Khairun; Nikayanti, Ria; Ritonga, Siti Meiranda Hafsari; Ardina, Lili; Siregar, Marniatun; Delima, Mas; Halawa, Sirina; Natunnah, Sofiyah; Nasution, Mutiah Dina; Rambe, Soleman Jufri (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
One of the goods that is needed by humans, both to maintain personal hygiene and environmental hygiene / sanitation is soap. Soap is a surfactant that is used with water for washing and cleaning. This community service aims to improve community skills in making dish soap through training conducted by the team. This activity uses a participatory model involving community components such as village heads, community leaders, environmental heads, and the community. The implementation of the activity was carried out with the main target being the Sitinjak Village community. The number of participants was 30 people. The location of this community service was carried out at the Sitinjak Village Head Office, Angkola Barat District, South Tapanuli Regency. This type of service is health promotion by providing information and demonstrations as well as training in making dish soap. The method used in this activity is in the form of training, discussion and question and answer. The visible end result of this training activity is that most people know the materials and tools needed in the process of making this dishwashing soap and know exactly the steps required in the manufacturing process. All activity participants stated that this community service was very useful because it could increase the community's knowledge and skills in making dishwashing soap.